Contesting inequality and worker mobilisation Australia 1851-1880 - Quinlan, Michael 1951- (Routledge, Taylor & Francis Group, 2021)
"Contesting Inequality and Worker Mobilisation: Australia 1851-1880 provides a new perspective on how and why workers organise, and what shapes that organisation. The author's 2018 Origins of Worker Mobilisation examined the beginning of worker organisation, arguing inequality at work, and regulatory subordination of labour, drove worker resistance, initially by informal organization that slowly transitioned to formal organisation. This new volume analyses worker mobilisation in the period 1851-1880, drawing data from a unique relational database recording every instance of organisation. It assesses not only the types of organization formed, but also the issues and objectives upon which mobilisation was founded. It examines the relationship between formal and informal organisation, including their respective influences in reshaping working conditions and the life-circumstances of working communities. It relates the examination of worker mobilisation to both historical and contemporary contexts and examines mobilisation by different categories of labour. The book identifies important effects of mobilisation on economic inequality, hours of work (including the eight-hour day and the beginnings of the weekend) and the development of democracy. It will be of interest to researchers, academics, and students in the fields of social mobilisation, social and economic history, industrial relations, labour regulation, labour history, and employment relations.
Includes bibliographical references and index
Keywords: 1851-1880; Arbeiterbewegung / (DE-627)091347351 / (DE-2867)16387-5; Gewerkschaftsbewegung / (DE-627)09136373X / (DE-2867)16629-0; Australien / (DE-627)091349044 / (DE-2867)17935-2; Labor unions / Australia / History / 19th century; Labor unions / Australia / History / 18th century; Equality / Australia / History / 19th century